Personalized peptide vaccination as second‐line treatment for metastatic upper tract urothelial carcinoma. Issue 12 (12th October 2017) - Suekane, Shigetaka; Ueda, Kousuke; Nishihara, Kiyoaki; Sasada, Tetsuro; Yamashita, Takuto; Koga, Noriko; Yutani, Shigeru; Shichijo, Shigeki; Itoh, Kyogo; Igawa, Tsukasa; Noguchi, Masanori
Abstract : This study investigated the applicability of personalized peptide vaccination (PPV) for patients with metastatic upper tract urothelial cancer (mUTUC) after failure of platinum‐based chemotherapy. In this single arm, open‐label, phase II clinical trial, patients with mUTUC received PPV at a single institution. Personalized peptide vaccination treatment used a maximum of four peptides chosen from 27 candidate peptides according to human leukocyte antigen types and peptide‐reactive IgG titers, for six s.c. injections weekly as one cycle. The safety of PPV, as well as its influence on host immunity and effect on overall survival were assessed. Forty‐eight patients were enrolled in this study. Personalized peptide vaccinations were well tolerated without severe adverse events. Median survival time was 7.3 months (95% confidence interval [CI], 5.3–13.1) with 13.0 months for patients receiving combined salvage chemotherapy (95% CI, 5.7–17.5) and 4.5 months for patients receiving PPV alone (95% CI, 1.7–10.1) ( P =  0.080). Patients with positive CTL responses showed a significantly longer survival than patients with negative CTL responses (hazard ratio, 0.37; 95% CI, 0.16–0.85; P  = 0.019). Multivariate Cox regression analysis showed that lower numbers of Bellmunt risk factors and lower levels of B‐cell activating factor were significantly associated with favorable overall survival for patients under PPV treatment. This study indicated that PPV for patients with mUTUC after failure of platinum‐based chemotherapy induced substantial peptide‐specific CTL responses without severe adverse events and has the potential to prolong survival when combined with salvage chemotherapy. UMIN Clinical Trials Registry ID: 000001854. Abstract : Prognostic significance of increased peptide‐specific CTL or IgG. Patients treated with PPV were divided into two subgroups according to CTL (A) responses. In addition, patients were divided into three subgroups with both positive CTL and IgG responses, positive CTL alone, positive IgG alone, or negative CTL and IgG (B).